Anne Frank: The Diary of a Young Girl: The Definitive Edition - Frank, Anne 1929-1945.; Blair, Selma (New York : Listening Library, 2010)
An uncut edition of Anne Frank's diary includes entries originally omitted by her father and provides insight into Anne's relationship with her mother.
Unabridged.
Compact discs.
Read by Selma Blair.
Keywords: Frank, Anne, -- 1929-1945 -- Diaries; Holocaust, Jewish (1939-1945) -- Personal narratives. -- Netherlands; Jews -- Persecutions -- Netherlands; Jews -- Diaries -- Netherlands; Audiobooks; Amsterdam (Netherlands) -- Ethnic relations